Dampak Pembangunan Taman Kasmaran Pada Perubahan Kondisi Ekonomi, Sosial-budaya Masyarakat, dan Lingkungan Kampung Wonosari - Lala Arastya Dewi; Retno Susanti (Jurusan Perencanaan Wilayah dan Kota, 2019)
The Mayor of Semarang revealed that Taman Kasmaran is one of the processes in structuring green open land in the city center. The development of Kasmaran Park is aimed at beautifying the Kampung Pelangi area. Thus, the Semarang City government changed the riverbanks of Semarang which was previously a slum into a productive area. The construction of the Kasmaran Park was completed at the end of 2017 and was inaugurated on January 8, 2018. The beginning of the land which is now the Kasmaran Park is a garage and barber shop area. The people of Kampung Wonosari are aware of the development of Kasmaran Park, but the majority of the people are not involved in the development process of Kasmaran Park. That is because the construction of the Kasmaran Park is a Semarang City government project. The method used is a quantitative method with frequency distribution analysis techniques and content analysis from questionnaire data distributed to 52 respondents. Based on the analysis that has been done, it can be concluded that the most felt impact for the people of Kampung Wonosari with the existence of Taman Kasmaran is on changing environmental conditions. That is because the existence of Taman Kasmaran brings environmental changes to be cleaner, and no longer slums. The community is becoming more concerned about the environment, the community also has a place for refreshing, a gathering place, recreation, playing with a better environment.